(untitled) (Società e diritti, 2017)
According to the author it is necessary to place the process of victimization in the field that Germán Silva called "divergence". The analysis sociology of crime seems useful because it is possible to delineate a continuum, scientifically identifiable and measurable, between situations in which the victimization is intertwined with conditions of poverty or economic marginality, and other characterized by gross violations of human rights in which human dignity is endangered (such as slavery or forced labour). Key words: Sociology of Law, Empirical research, Criminology